(untitled) (Geograficidade, 2016)
Resenha do livro KOENIG, Harold G. Medicina, Religião e Saúde: o Encontro da ciência e da espiritualidade. Editora L&PM, 1a. ed., 2012. 248p. ISBN: 978-85-2542-719-9.